2015
DOI: 10.1111/jopr.12420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Gastric Juice on CAD/CAM Resin Composites—Morphological and Mechanical Evaluations

Abstract: The acidic scenario tested in the present study changed the surface roughness of the resin composites but not their Vickers microhardness. Moreover, both resin composites seem suitable for use under acidic scenarios, although Paradigm MZ100 showed enhanced stability compared to Lava Ultimate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 43 publications
7
55
0
Order By: Relevance
“…The second hypothesis "Challenges can generate alterations in surface roughness, surface loss, and biofilm deposition of the glaze layer" was accepted. Concerning the challenges to which the glaze was exposed, Hunt 13,14,20,21 In this study, the erosive protocol employed generated a significant reduction in the Ra value of the glaze layer, which agree with previous studies, 14,[22][23][24][25] In this study, the abrasive challenge aimed to simulate the mean force applied by an individual while brushing over 3 years. 26,27 Also, brush replacement corresponded to approximately 4 months of brushing, according to the current American Dental Association (ADA) recommendation, 28 which corresponds to 50 000 strokes performed in this study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The second hypothesis "Challenges can generate alterations in surface roughness, surface loss, and biofilm deposition of the glaze layer" was accepted. Concerning the challenges to which the glaze was exposed, Hunt 13,14,20,21 In this study, the erosive protocol employed generated a significant reduction in the Ra value of the glaze layer, which agree with previous studies, 14,[22][23][24][25] In this study, the abrasive challenge aimed to simulate the mean force applied by an individual while brushing over 3 years. 26,27 Also, brush replacement corresponded to approximately 4 months of brushing, according to the current American Dental Association (ADA) recommendation, 28 which corresponds to 50 000 strokes performed in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Concerning the challenges to which the glaze was exposed, Hunt and McIntyre 13 suggested an erosive protocol to simulate oral conditions from intrinsic acid from gastroesophageal reflux disease, simulating 3 years of the in vivo condition 14 . Even though there is no consensus in the literature regarding the optimal protocol for gastric erosion, several authors have shown that the most viable alternative to simulate gastric juice is the use of a hydrochloric acid solution 13,14,20,21 . In this study, the erosive protocol employed generated a significant reduction in the Ra value of the glaze layer, which agree with previous studies, 14,22‐25 indicating that these materials are susceptible to degradation in low pH environments.…”
Section: Discussionsupporting
confidence: 76%
“…However, the materials were tested without exposure to an acidic drink, in contrast to the present study. Another report [26] evaluated the effects of simulated gastric juice on the mechanical properties of a CAD/CAM resin composite (i.e., micro-hardness). The acid scenario (immersion in an acidic solution for 6 and 24 h) did not change their micro-hardness.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies evaluating wear resistance and other mechanical properties of resin‐matrix ceramic materials were conducted with only one type of storage media, no comparisons can be made regarding the effects of different storage media on the wear of resin‐matrix ceramics. While both Lava Ultimate and Paradigm MZ100 have been shown to be susceptible to roughening under acidic conditions due to the hydrolysis of the methacrylate ester bonds in their polymer matrixes, whether there is a direct correlation between the surface roughness and wear rates of these materials has yet to be investigated. Moreover, the present study's findings regarding the effects of storage material and wear conflict with those of Yap et al, who reported chemical degradation in the mouth to be a major factor in the amount of wear on the occlusal contact surfaces of composite restorations.…”
Section: Resultsmentioning
confidence: 99%